Nonlinear signal time-frequency analysis method based on short-time fractional order Fourier transform - ZHANG XIUMEI; HOU HUILING; ZHUO HUI; HAN YAN; PANG CUNSUO (2017)
The invention discloses a nonlinear signal time-frequency analysis method based on short-time fractional order Fourier transform, and the nonlinear signal time-frequency analysis method belongs to the technical field of target signal analysis. The nonlinear signal time-frequency analysis method utilizes short-time fractional order Fourier transform, subjects a signal to segmentation processing and combined processing of different orders of fractional order Fourier transform through short-time fractional order Fourier transform, adopts an angle constraint method for fractional-order order searching, improves the time-frequency resolution of the target signal and the precision of time-frequency analysis, completes the time-frequency analysis of single-component and multi-component nonlinear signals, solves the problems of low time-frequency resolution and difficult separation of the target nonlinear echo signal, is conductive to parameter estimation of the weak target signal, improve the precision of signal par